Foreign Direct Investment in the U.S., 1974–1984 - Arpan, Jeffrey S.; Ricks, David A. (Journal of International Business Studies, 1986)
Foreign Direct Investment (FDI) in the United States has become more important but less sensationalized over the past dozen years. This note compares the pattern of FDI as of 1974, 1978 and 1984 and concludes that the pattern has remained more consistent than might have been expected. The number of foreign-owned firms has risen dramatically, but the foreign investments tend to be in the same states and industries and from the same countries as they were in 1974. Exceptions to these norms are noted.